Design and development of bio-inspired underwater jellyfish like robot using ionic polymer metal composite (IPMC) actuators - Akle, Barbar (2011)
This study presents the design and development of an underwater Jellyfish like robot using Ionic Polymer Metal Composites (IPMCs) as propulsion actuators. For this purpose, IPMCs are manufactured in several variations. First the electrode architecture is controlled to optimize the strain, strain rate, and stiffness of the actuator. Second, the incorporated diluents species are varied. The studied diluents are water, formamide, and 1-ethyl-3-methyimidazolium trifluoromethanesulfonate (EmI-Tf) ionic liquid. A water based IPMC demonstrates a fast strain rate of 1%/s, but small peak strain of 0.3%, and high current of 200mA/cm2, as compared to an IL based IPMC which has a slow strain rate of 0.1%/s, large strain of 3%, and small current of 50mA/cm2. The formamide is proved to be the most powerful with a strain rate of approximately 1%/s, peak strain larger than 5%, and a current of 150mA/cm2. The IL and formamide based samples required encapsulation for shielding the diluents from being dissolved in the surrounding water. Two Jellyfish like robots are developed each with an actuator with different diluents. Several parameters on the robot are optimized, such as the input waveform to the actuators, the shape and material of the belly. The finesse ratio of the shape of the robotic belly is compared with biological jellyfish such as the Aurelia-Aurita..